Mini-FLOTAC for the diagnosis of Eimeria infection in goats: An alternative to McMaster - Silva, L.M.R. (2014)
Caprine coccidiosis is responsible for remarkable economic losses. Diagnosis must therefore take into account a number of epidemiological and clinical factors supported by laboratory investigations. The detection of Eimeria oocysts and the determination of oocysts per gram of faeces (OPG) require a trustworthy oocyst count technique. Mini-FLOTAC is a new apparatus from the FLOTAC family, which was designed for optimal examination of faecal sample suspensions in each flotation chamber (total volume = 2 mL) and which permits a maximum magnification of 400x. Faecal samples from sixteen goats reared in an intensive goat farm were qualitatively (simple flotation) and quantitatively analyzed. A comparison between McMaster (McM) and Mini-FLOTAC was carried out, by performing 288 different readings. Eimeria arloingi, E. caprovina and E. ninakohlyakimovae were the most prevalent species. The mean OPG detected by Mini-FLOTAC was higher than the values observed with McMaster techniques (P<0.05). Mini-FLOTAC also produced coefficient of variation values similar to those resulted from McM 1 mL (17.5 versus 19.4; P>0.05) but lower than those resulted from McM 0.3 mL. Thereby, the present study suggests that the Mini-FLOTAC is a promising technique for detecting and counting Eimeria spp. in goat faeces.